Prinsip-Prinsip Pendampingan Generasi yang Fatherless menurut 1 Tesalonika 2:7 - Novianti, Novianti; Baskoro, Paulus Kunto (KARDIA: Jurnal Teologi dan Pendidikan Kristiani, 2025)
Abstract: The phenomenon of "fatherlessness," or the absence of a father figure, has become an increasingly concerning social issue, including in Indonesia. Children growing up without a father face various negative impacts, such as psychological disorders, difficulties in forming self-identity, and increased involvement in risky behaviours. The church has the potential to act as an agent of restoration through mentoring based on love and spiritual values. This study aims to examine the church’s mentoring principles for the "fatherless" generation based on 1 Thessalonians 2:7 and identify its implications and logical applications in church life. This study employs a qualitative approach with a hermeneutic analysis of 1 Thessalonians 2:7 and a literature review from relevant books and journals. The findings indicate that church mentoring for the "fatherless" generation can be realized through a gentle and loving approach, effective discipleship, character and identity formation, and emotional healing. The church can also function as a community that provides spiritual and psychosocial support for children who lack a father figure. The implications of this study emphasize that the church must develop a sustainable discipleship system, instil Christ-centered values, and create a supportive environment for young people experiencing "fatherlessness." The novelty of this research lies in its perspective on spiritually-based mentoring, highlighting the church’s role as a "home" for those who have lost a father figure. Abstrak: Fenomena "fatherlessness" atau kehilangan figur ayah menjadi isu sosial yang semakin mengkhawatirkan, termasuk di Indonesia. Anak-anak yang tumbuh tanpa kehadiran ayah mengalami berbagai dampak negatif, seperti gangguan psikologis, kesulitan dalam membentuk identitas diri, serta keterlibatan dalam perilaku berisiko. Gereja memiliki potensi untuk berperan sebagai agen pemulihan melalui pendampingan yang berbasis kasih dan nilai-nilai spiritual. Penelitian ini bertujuan untuk mengkaji prinsip pendampingan gereja bagi generasi "fatherless" berdasarkan 1 Tesalonika 2:7, serta mengidentifikasi implikasi dan penerapan logisnya dalam kehidupan gerejawi. Metode yang digunakan dalam penelitian ini adalah pendekatan kualitatif dengan analisis hermeneutik terhadap teks 1 Tesalonika 2:7 serta kajian pustaka dari buku dan jurnal yang relevan. Hasil penelitian menunjukkan bahwa pendampingan gereja bagi generasi "fatherless" dapat diwujudkan melalui pendekatan lembut dan penuh kasih, pemuridan yang efektif, pembentukan karakter dan identitas diri, serta penyembuhan emosional. Gereja juga dapat berfungsi sebagai komunitas yang memberikan dukungan spiritual dan psikososial bagi anak-anak yang kehilangan figur ayah. Implikasi dari penelitian ini menegaskan bahwa gereja harus mengembangkan sistem pemuridan yang berkelanjutan, menanamkan nilai-nilai kasih Kristus, dan menciptakan lingkungan yang mendukung bagi generasi muda yang mengalami "fatherlessness". Kebaruan penelitian ini terletak pada perspektif pendampingan berbasis spiritual yang menekankan peran gereja sebagai "rumah" bagi mereka yang kehilangan figur ayah.